Excisionase in Pf filamentous prophage controls lysis‐lysogeny decision‐making in Pseudomonas aeruginosa. Issue 2 (12th December 2018) - Li, Yangmei; Liu, Xiaoxiao; Tang, Kaihao; Wang, Pengxia; Zeng, Zhenshun; Guo, Yunxue; Wang, Xiaoxue
Summary: Pf filamentous prophages are prevalent among clinical and environmental Pseudomonas aeruginosa isolates. Pf4 and Pf5 prophages are integrated into the host genomes of PAO1 and PA14, respectively, and play an important role in biofilm development. However, the genetic factors that directly control the lysis‐lysogeny switch in Pf prophages remain unclear. Here, we identified and characterized the excisionase genes in Pf4 and Pf5 (named xisF4 and xisF5, respectively). XisF4 and XisF5 represent two major subfamilies of functional excisionases and are commonly found in Pf prophages. While both of them can significantly promote prophage excision, only XisF5 is essential for Pf5 excision. XisF4 activates Pf4 phage replication by upregulating the phage initiator gene ( PA0727 ). In addition, xisF4 and the neighboring phage repressor c gene pf4r are transcribed divergently and their 5′‐untranslated regions overlap. XisF4 and Pf4r not only auto‐activate their own expression but also repress each other. Furthermore, two H‐NS family proteins, MvaT and MvaU, coordinately repress Pf4 production by directly repressing xisF4 . Collectively, we reveal that Pf prophage excisionases cooperate in controlling lysogeny and phage production. Abstract : A proposed model of the lysis‐lysogeny switch of Pf4 in PAO1. Integration of Pf4 in host genome is maintained by MvaT/MvaU by binding to the excisionase gene xisF4 . Inactivation of MvaT/MvaU upregulates xisF4 and subsequently, XisF4 activates the replication initiator gene PA0727, leading to Pf4 phage replication and release.